2022
DOI: 10.1021/acsomega.2c01420
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties and Reliabilities of Lauric Acid-Based Binary Eutectic Fatty Acid as a Phase Change Material for Building Energy Conservation

Abstract: Thermal properties, stability, and reliability of lauric acid-based binary eutectic mixtures for building energy efficiency were studied. The eutectic points and phase change performance of these binary PCMs were obtained as follows: (1) For lauric acid–myristic acid, the mass eutectic point is 70 wt % LA/30 wt % MA. (2) For lauric acid–palmitic acid, the eutectic point is 79 wt % LA/21 wt % PA. (3) For lauric acid–stearic acid, the eutectic point is 82 wt % LA/18 wt % SA. The eutectic PCMs have a melting enth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In our previous study, the eutectic mass ratio of L–S was determined to be 82 : 18 by step-cooling curve experiments and DSC analysis. 32 The LS/EP CPCMs were synthesized using the vacuum impregnation process shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, the eutectic mass ratio of L–S was determined to be 82 : 18 by step-cooling curve experiments and DSC analysis. 32 The LS/EP CPCMs were synthesized using the vacuum impregnation process shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%
“…After analysing them through various tests it was concluded that both PCMs were suitable for self-compacting concrete mixtures used in buildings. Dai et al [27] prepared composite PCMs with good properties and suitable phase change temperatures by combining different fatty acids. They found that multiple PCMs can indeed extend the phase change temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] Through eutectic behavior, it is possible to modify the crystallization temperature, particulate size, and enthalpy of binary or tribasic fatty acid complex systems. 35,37 Lauric acid is a type of "reactive emulsifier," because it could undergo a chelation reaction with calcium ions in cement due to its carboxylic acid groups. [38][39][40] The use of reactive emulsifier lauric acid for the preparation of low-viscosity stearic acid emulsion not only solves the problem of inadequate dispersion of stearic acid powder in cement, but also solves the problem of water absorption of residual emulsifier in mortar.…”
Section: Introductionmentioning
confidence: 99%
“…The fatty acids lauric acid, palmitic acid, and oleic acid exhibit eutectic behavior with stearic acid during melt merging, according to studies 34–36 . Through eutectic behavior, it is possible to modify the crystallization temperature, particulate size, and enthalpy of binary or tribasic fatty acid complex systems 35,37 . Lauric acid is a type of “reactive emulsifier,” because it could undergo a chelation reaction with calcium ions in cement due to its carboxylic acid groups 38–40 .…”
Section: Introductionmentioning
confidence: 99%